Hitung Diferensial dan Kelainan-Kelainan Sel Darah Sapi Bali (DIFFERENTIAL COUNT AND ABNORNALITIES OF BALI CATTLE BLOOD CELLS) - Utama, Iwan Harjono; Kendran, Anak Agung Sagung; Widyastuti, Sri Kayati; Virgania, Putri; Sene, Sherliyanti Maria; Kusuma, Widarta Dwi; Arisandi, Baiq Yunita (Jurnal Veteriner, 2013)
Research on blood smear and various disorder in Bali cattle have been conducted at 124 oxen and 76cows. Blood specimens taken from cattle slaughtered cattle in Slaughterhouse Mambal Badung Regency,Bali and blood smear were performed   by a method described elsewhere.Results showed the mean of differential count of lymphocytes, monocytes, neutrophils, eosinophils, basophilsand bands in female Bali cattle bands respectively (average + standard deviation): (47.76 ± 12.13)%, (9.84± 5, 32)%, (39.09 ± 12.55)%, (2.25 ± 2.40)%, (0.33 ± 1.18)%, (0.21 ± 1.01)%. In bali cattle males, thoseresults were : (46.48 ± 8.18)%, (9.84 ± 4.35)%, (40.51 ± 8.29)%, (1.48 ± 1.69)%; (0.45 ± 0.84)%, (0.57 ±0.99)%. Abnormalities that were found are: eosinophenia, monocytosis, Neutrophilia, lymphopenia andlymphocytosis, anisocytosis, poikilocytosis (the presence of akhantocytes, dacrocyt), and hypochromasia.In summary Bali cattle are observed to have abnormalities in the blood cells.
Keywords: bali cattle blood smear